Tailoring Metal–Oxide Interfaces via Selectively CeO2-Decorated Pd Nanocatalysts with Enhanced Catalytic Performance - Ziwen Liu; Guizhen Zhang; Lijuan Niu; Zaicheng Sun; Zhenguo Li; Hong He (Nanomaterials)
Metal–oxide interfaces play a prominent role in heterogeneous catalysis. Tailoring the metal–oxide interfaces effectively enhance the catalytic activities and thermal stability of noble metal catalysts. In this work, polyvinyl alcohol-protected reduction and L-arginine induction methods are adopted to prepare Pd catalysts (Pd/Al2O3-xCeO2) that are selectively decorated by CeO2, which form core–shell-like structures and generate more Pd-CeO2 interfacial sites, so that the three-way catalytic activity of Pd/Al2O3-xCeO2 catalysts is obviously significantly enhanced due to more adsorption oxygen at the interface of Pd-CeO2 and good low-temperature reducibility. At the moment, the Pd/Al2O3-xCeO2 catalysts exhibit excellent thermal stability after being calcined at 900 °C for 5 h, owing to the Pd species being highly redispersed on CeO2 and part of the Pd species being incorporated into the lattice of CeO2. This is a major reason for the Pd/Al2O3-xCeO2 catalysts to maintain high catalytic activity after aging at high temperatures. It is concluded that the metal–oxide interfaces and the interaction between Pd NPs and CeO2 are responsible for the excellent catalytic performance and stability of Pd/Al2O3-xCeO2 catalysts in three-way reactions.